FORMULATION AND EVALUATION OF SEA GRAPE (Caulerpa racemose) EXTRACT AS HAND CREAM AND ITS ANTIOXIDANT ACTIVITY TEST - Septilina Melati Sirait; Tita Rosita; Lintannisa Rahmatia (Jurnal Kimia Riset, 2022)
Caulerpa racemosa (C. racemosa) is a seaweed containing folic acid, thiamine, ascorbic acid, and phenol as secondary metabolites that function as antioxidants. This study aims to formulate a hand moisturizing cream containing C. racemosa extract and evaluate the quality of the cream preparation. The manufacture of hand cream from C. racemosa extract was carried out in several stages, namely C. racemosa extraction, antioxidant testing, formulation of cream preparations, and evaluation. Evaluation of hand cream preparations of C. racemosa extract included organoleptic tests, homogeneity, pH measurement, viscosity, spreadability, and adhesion. The yield of C. racemosa from the extract was 33%. The IC50 of the C. racemosa extract was 159.8 ppm. The results of the organoleptic test of hand cream preparations showed physical characteristics in terms of pH, viscosity, homogeneity, dispersibility, and adhesion following the requirements of cosmetic preparations from the Directorate General of BPOM.